Electron Transfer Mediated by Surface‐Tethered Redox Groups in Nanofluidic Devices. Issue 8 (16th December 2016) - Steentjes, Tom; Sarkar, Sahana; Jonkheijm, Pascal; Lemay, Serge G.; Huskens, Jurriaan
Abstract : Electrochemistry provides a powerful sensor transduction and amplification mechanism that is highly suited for use in integrated, massively parallelized assays. Here, the cyclic voltammetric detection of flexible, linear poly(ethylene glycol) polymers is demonstrated, which have been functionalized with redox‐active ferrocene (Fc) moieties and surface‐tethered inside a nanofluidic device consisting of two microscale electrodes separated by a gap of <100 nm. Diffusion of the surface‐bound polymer chains in the aqueous electrolyte allows the redox groups to repeatedly shuttle electrons from one electrode to the other, resulting in a greatly amplified steady‐state electrical current. Variation of the polymer length provides control over the current, as the activity per Fc moiety appears to depend on the extent to which the polymer layers of the opposing electrodes can interpenetrate each other and thus exchange electrons. These results outline the design rules for sensing devices that are based on changing the polymer length, flexibility, and/or diffusivity by binding an analyte to the polymer chain. Such a nanofluidic enabled configuration provides an amplified and highly sensitive alternative to other electrochemical detection mechanisms. Abstract : Electrodes of nanogap devices are grafted with linear poly(ethylene glycol) polymers functionalized with a redox‐active ferrocene moiety. Electrons are shuttled between the two electrodes by the diffusion of the attached ferrocene moieties in the absence of a redox mediator, resulting in an amplified steady state current that can be tuned by variation of the polymer length and density.